Influence of longswing technique on the kinematics and key release parameters of the straddle Tkachev on uneven bars - Manning, M. L.; Irwin, G.; Gittoes, M. J. R.; Kerwin, D. G. (Sports Biomechanics, 2011)
Tkachev on uneven bars is a release and re-grasp skill performed using variations of preparatory longswing techniques; the reasons why different techniques are chosen remains unclear. This study examined kinematic and key release parameters specific to three distinct techniques with the aim of understanding the relative benefits of each. During two international artistic gymnastics competitions six arch, straddle and pike longswings preceding the straddle Tkachev were recorded using twin video cameras. Calibration and movement images were digitised and reconstructed using 3D DLT. Shoulder and hip angular kinematics, angular momentum and key release parameters were compared between techniques. In the arch longswing, the first and second hip functional phases began significantly earlier than the straddle or pike. No significant differences were established for release parameters although large effect sizes for horizontal release velocity and angular momenta about the mass centre and bar were reported between the arch and other two variants. Therefore, the arch variant may provide the opportunity to develop more complex combinations following the Tkachev. Providing insight into mechanical advantages of specific longswing techniques, and highlighting those that elicit desirable characteristics offers the potential to provide coaches with objective data on technique selection and ultimately skill development.